Manganese-Enhanced T1 Mapping in the Myocardium of Normal and Infarcted Hearts. (25th October 2018) - Spath, N. B.; Lilburn, D. M. L.; Gray, G. A.; Le Page, L. M.; Papanastasiou, G.; Lennen, R. J.; Janiczek, R. L.; Dweck, M. R.; Newby, D. E.; Yang, P. C.; Jansen, M. A.; Semple, S. I.
Abstract : Background . Manganese-enhanced MRI (MEMRI) has the potential to identify viable myocardium and quantify calcium influx and handling. Two distinct manganese contrast media have been developed for clinical application, mangafodipir and EVP1001-1, employing different strategies to mitigate against adverse effects resulting from calcium-channel agonism. Mangafodipir delivers manganese ions as a chelate, and EVP1001-1 coadministers calcium gluconate. Using myocardial T1 mapping, we aimed to explore chelated and nonchelated manganese contrast agents, their mechanism of myocardial uptake, and their application to infarcted hearts. Methods . T1 mapping was performed in healthy adult male Sprague-Dawley rats using a 7T MRI scanner before and after nonchelated (EVP1001-1 or MnCl2 (22  μ mol/kg)) or chelated (mangafodipir (22–44  μ mol/kg)) manganese-based contrast media in the presence of calcium channel blockade (diltiazem (100–200  μ mol/kg/min)) or sodium chloride (0.9%). A second cohort of rats underwent surgery to induce anterior myocardial infarction by permanent coronary artery ligation or sham surgery. Infarcted rats were imaged with standard gadolinium delayed enhancement MRI (DEMRI) with inversion recovery techniques (DEMRI inversion recovery) as well as DEMRI T1 mapping. A subsequent MEMRI scan was performed 48 h later using either nonchelated or chelated manganese and T1 mapping. Finally, animals were culled at 12 weeks, and infarct size was quantified histologically with Masson's trichrome (MTC). Results . Both manganese agents induced concentration-dependent shortening of myocardial T1 values. This was greatest with nonchelated manganese, and could be inhibited by 30–43% with calcium-channel blockade. Manganese imaging successfully delineated the area of myocardial infarction. Indeed, irrespective of the manganese agent, there was good agreement between infarct size on MEMRI T1 mapping and histology (bias 1.4%, 95% CI −14.8 to 17.1P > 0.05 ). In contrast, DEMRI inversion recovery overestimated infarct size (bias 11.4%, 95% CI −9.1 to 31.8P = 0.002 ), as did DEMRI T1 mapping (bias 8.2%, 95% CI −10.7 to 27.2P = 0.008 ). Increased manganese uptake was also observed in the remote myocardium, with remote myocardial ∆T1 inversely correlating with left ventricular ejection fraction after myocardial infarction (r = − 0.61, P = 0.022 ). Conclusions . MEMRI causes concentration and calcium channel-dependent myocardial T1 shortening. MEMRI with T1 mapping provides an accurate assessment of infarct size and can also identify changes in calcium handling in the remote myocardium. This technique has potential applications for the assessment of myocardial viability, remodelling, and regeneration.